Facial profile analysis by photometry among elementary school students: an observational analytic study - Putri Taghna, Zahradena Shafira; Sulistiyani, Sulistiyani; Setyorini, Dyah; Prihatiningrum, Berlian; Probosari, Niken; Sukanto, Sukanto; Rahardjo, Roedy Budi; Novita, Masniari; Anthony, Osunwoke Emeka (Padjadjaran Journal of Dentistry, 2024)
Introduction: The facial profile refers to the anteroposterior relationship visible from the lateral view of the face. There are three types of the facial profile: straight, convex, and concave. Photometry is a reliable, simple and accurate methods for determining the facial profile. Facial profile can be influenced by various factors, such as genetics, gender, age, and environment. This study aims to analyze the differences in facial profiles between male and female elementary school students. Methods: an observational analytic with a cross-sectional design. The subjects were elementary school students in Jember Regency, aged 6-12 years. A of 141 children participated in the study, consisting of 76 males and 65 females. Data analysis included Kolmogorov-Smirnov normality test, the Levene test for homogeneity, and an independent parametric t-Test to compare the facial profiles of males and females. Results: The average facial profile angle among elementary school students shows a straight facial profile. The average angle for females was 157.71º, which was slightly greater than that of males. However, there was no significant difference between male and female facial profiles. Similarly, no significant difference observed between the facial profiles of students aged 6-9 years old and those aged 10-12 years old. Conclusion: Elementary school students predominantly exhibit straight facial profiles, with this profile being more common among males.